2017
DOI: 10.1093/nar/gkx682
|View full text |Cite
|
Sign up to set email alerts
|

Novel cell surface luciferase reporter for high-throughput yeast one-hybrid screens

Abstract: Gene-centered yeast one-hybrid (Y1H) screens provide a powerful and effective strategy to identify transcription factor (TF)-promoter interactions. While genome-wide TF ORFeome clone collections are increasingly available, screening protocols have limitations inherent to the properties of the enzymatic reaction used to identify interactions and to the procedure required to perform the assay in a high-throughput format. Here, we present the development and validation of a streamlined strategy for quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…We further tested a group of SPL and TCP factors with a second Y1H system, based on a secreted luciferase reporter with an improved dynamic range (Bonaldi et al., ); repeated testing reduces statistical false positives and use of alternative reporters can reveal reporter‐gene‐specific technical false positives (Walhout, ). This secondary screening confirmed that multiple SPL and TCP TFs bind the second proximal AGO7 promoter fragment tested, despite considerable experimental variability (Supporting Information Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We further tested a group of SPL and TCP factors with a second Y1H system, based on a secreted luciferase reporter with an improved dynamic range (Bonaldi et al., ); repeated testing reduces statistical false positives and use of alternative reporters can reveal reporter‐gene‐specific technical false positives (Walhout, ). This secondary screening confirmed that multiple SPL and TCP TFs bind the second proximal AGO7 promoter fragment tested, despite considerable experimental variability (Supporting Information Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Diploid cells were selected in media lacking uracil and tryptophan, lysed by freeze‐thaw, and assayed for β‐galactosidase activity. Targeted Y1H assays were done similarly, with the lysis and assay steps replaced, essentially as described (Bonaldi et al., ). Briefly, diploid cells were resuspended in phosphate‐buffer saline, 50 μl of cells were transferred to a clear‐bottom plate, and a Synergy H1 plate reader (Biotek) was used to inject 10 μl of 20 μM coelenterazine substrate solution into each well and read luminescence immediately afterward (0.1 s integration time).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following points should be considered when performing these protocols: Each deep 384‐well microplate containing the TF‐gal4AD clone collection in YU yeast cells must include 4 to 6 wells without YU cells (empty well controls) and 4 to 6 wells containing YU cells transformed with the empty AD vector (i.e., pEXP‐AD for libraries in pDEST22) (empty vector control) (Kang et al., ; Pruneda‐Paz et al., ). Grow enriched diploid yeast cells in YPD for 5 to 6 hr prior gLUC activity quantification. Homogenize cell suspension in absorbance and luminescence microplates before placing into microplate reader. Avoid air bubbles after dispensing the cell culture into the absorbance microplates. Do not use gLUC substrate solution immediately after preparation (stabilize for 30 min prior usage). Determine gLUC activity directly in a cell culture aliquot (washing cells before measurement results in lower luminescence) (Bonaldi et al., ). Consider that while flash luminescence provides the most sensitive assay, it will require significantly longer microplate reader processing time. For glow luminescence quantification, incubate microplates for 8 to 10 min before measurement to avoid result bias across wells due to luminescence decay (Bonaldi et al., ). To minimize false positive calls, identify and eliminate from further analysis wells with no yeast cell growth. …”
Section: Commentarymentioning
confidence: 99%
“…On the other hand, reporter genes for auxotrophic selection (e.g., HIS3 ) and/or colorimetric detection (e.g., lacZ ) were used to identify positive interactions in a high‐throughput multi‐well format (Pruneda‐Paz et al., ; Reece‐Hoyes et al., ). Recently, we implemented a novel cell surface luciferase reporter (gLUC59) that significantly improved the simplicity, reliability, and scalability of HT‐Y1H screens compared to our previous method using the lacZ reporter gene (Bonaldi, Li, Kang, Breton, & Pruneda‐Paz, ; Pruneda‐Paz et al., ). Here, we described the procedure to perform HT‐Y1H screens using the gLUC59 reporter, which involves automation‐compatible protocols to deliver a TF clone collection into yeast reporter strains, and to quantify gLUC59 activity and determine screen results (Fig.…”
Section: Introductionmentioning
confidence: 99%